Effect Of Cucumber Juice And Brisk Walking Exercise On Blood Pressure In Elderly Hypertension Patients - Nufus Chalida; Era Ziadatul; Felyn Melati; Maulinda Dwi; Angga Sugiarto (Midwifery and Nursing Research, 2019)
Background- The treatment for lowering blood pressure can be pharmacological therapy with drugs and also non-pharmacological therapy. Cucumber juice and brisk walking exercise are non-pharmacological therapy that can be done with.Purpose - Knowing the effect of cucumber juice and brisk walking exercise on blood pressure in elderly hypertensive patientsMethod- This research is quasi experiment with pretest and posttest design, using purposive sampling with amount of 40 respondents who were draw with certain inclusion criteria. Data analysis used to assess the differences in the group with paired t-test and between groups using Independent t tests.Results- The test results paired t test in the intervention group cucumber juice systolic blood pressure and diastolic p = 0.00 p = 0.00. The test results paired t test in the group of brisk walking exercise systolic blood pressure and diastolic p = 0.01 p = 0.03. Independent test t test in the intervention group cucumber juice and brisk walking exercise with the results systole and diastole p = 0.017 p = 0.04 (0.05), which indicates that there is a difference in blood pressure between the groups cucumber and group therapy exercise brisk walking. On the intervention of cucumber juice for 7 days can lower systolic blood pressure of 10.2 mm Hg and diastolic blood pressure of 8.9 mmHg. While the intervention brisk walking exercise to lower blood pressure 4 mmHg systolic blood pressure and 3.5 mmHg diastol.Conclusion - Intervention cucumber juice is more effective than intervention of brisk walking exercise in lowering blood pressure of elderly patients with hypertension.